2010
DOI: 10.2478/s11687-010-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infections of the European brown hare (Lepus europaeus Pallas, 1778) in south -western Slovakia

Abstract: A total of 74 European brown hares (Lepus europaeus Pallas, 1778), hunted during the winter seasons of 2006 and 2007, were examined by dissection for the presence of helminths and coprologically for protozoa. The animals came from five districts with a high population density of this species. Our results revealed 54.5 % of specimens being infected with one or more helminth species and a high prevalence of eimeriid coccidia (91.89 %). The most prevalent helminth species was Trichuris leporis (55.41 %). Lower pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
10
1
1
Order By: Relevance
“…Although (Wibbelt & Frölich, 2005). The prevalence of this parasite in the present study was 21.42 %, while it has been reported in higher percentages in central and northern Europe in the past (Sebek, 1969;Irvin, 1970;Dubinský et al, 2010). Larvae (L1) of the lung nematode Protostrongylus sp.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Although (Wibbelt & Frölich, 2005). The prevalence of this parasite in the present study was 21.42 %, while it has been reported in higher percentages in central and northern Europe in the past (Sebek, 1969;Irvin, 1970;Dubinský et al, 2010). Larvae (L1) of the lung nematode Protostrongylus sp.…”
Section: Discussionmentioning
confidence: 37%
“…However, a relatively low prevalence i.e. 6.76 % was recorded in Slovakia (Dubinský et al, 2010). Severe infections by this parasite can result in chronic enteritis, with hyperaemia, petechiae and epithelial erosions (Chroust et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Newey et al (2005) reported that T. retortaeformis infection results in a strong reduction in the body condition and fertility of females but does not influence their survival. On the other hand, a surprisingly low intensity of infection by T. retortaeformis was recently reported in brown hares from Slovak Republic (Dubinsky et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of the endoparasites of European hares were conducted in the latter half of the twentieth century (Haupt & Hartung, 1976;Kutzer & Frey, 1976;Nickel & Gottwald, 1979;Forstner & Ilg, 1982;Soveri & Valtonen, 1983;Pakandl, 1990;Allgöwer, 1992;Böckeler et al, 1994). Recently, studies have become rarer i.e., from France by Bordes et al (2007), from Poland by Pilarczyk et al (2008) and from Slovakia by Dubinský et al (2010). The objectives of this study were as follows: 1) to observe the prevalence and abundance of gastrointestinal (GI) parasites of European hares in game keeping shooting-ground conditions during two winter seasons, 2) to monitor seasonal dynamics of exogenous stage excretion during the winter and spring season.…”
Section: Introductionmentioning
confidence: 99%